Critical edition of the Peruvian Traditions of Ricardo Palma - Díaz Ortiz, Pedro (2020)
The critical edition of the First and Second Series of Peruvian Traditions by Ricardo Palma was published in 2008 and 2019 respectively. In this article, we emphasize how Ricardo Palma modified his traditions in every edition, and, as a sample of this labor, we publish the tradition Una aventura del virrey-poeta that belongs to the Third Series of Peruvian Traditions.